Adipose stromal cell-derived secretome attenuates cisplatin-induced injury in vitro surpassing the intricate interplay between proximal tubular epithelial cells and macrophages - Rendra, Erika; Uhlig, Stefanie; Moskal, Isabell; Thielemann, Corinna; Klüter, Harald; Bieback, Karen (Cells, 2024)
(1) Background: The chemotherapeutic drug cisplatin exerts toxic side effects causing acute kidney injury. Mesenchymal stromal cells can ameliorate cisplatin-induced kidney injury. We hypothesize that the MSC secretome orchestrates the vicious cycle of injury and inflammation by acting on proximal tubule epithelial cells (PTECs) and macrophages individually, but further by counteracting their cellular crosstalk. (2) Methods: Conditioned medium (CM) from adipose stromal cells was used, first assessing its effect on cisplatin injury in PTECs. Second, the effects of cisplatin and the CM on macrophages were measured. Lastly, in an indirect co-culture system, the interplay between the two cell types was assessed. (3) Results: First, the CM rescued PTECs from cisplatin-induced apoptosis by reducing oxidative stress and expression of nephrotoxicity genes. Second, while cisplatin exerted only minor effects on macrophages, the CM skewed macrophage phenotypes to the anti-inflammatory M2-like phenotype and increased phagocytosis. Finally, in the co-culture system, the CM suppressed PTEC death by inhibiting apoptosis and nuclei fragmentation. The CM lowered TNF-α release, while cisplatin inhibited macrophage phagocytosis, PTECs, and the CM to a greater extent, thus enhancing it. The CM strongly dampened the inflammatory macrophage cytokine secretion triggered by PTECs. (4) Conclusions: ASC-CM surpasses the PTEC-macrophage crosstalk in cisplatin injury. The positive effects on reducing cisplatin cytotoxicity, on polarizing macrophages, and on fine-tuning cytokine secretion underscore MSCs’ CM benefit to prevent kidney injury progression.
Gesehen am 26.09.2024